Perforating urinary bladder foreign body managed with minimally invasive surgery - Laha, Ishita; Hameed, Shahid; Sen, Swapnil; Sarkar, Kalyan Kumar (Eastern Journal of Medical Sciences, 2021)
Foreign bodies are occasionally reported in the urinary bladder, especially in females. The consequences and clinical impact depend on the route of insertion and the patient’s hemodynamic condition, and their removal may include minimally invasive procedures to open cystostomy. In most cases, foreign bodies are removed through transurethral approach. Here, we report one such case of a foreign body in the urinary bladder, which was self-inserted and had perforated through the bladder wall, yet could be successfully managed by cystoscopic removal without any complications.